Design of E-Module Based on Discovery Learning in Basic Boga Students of Class X Tata Boga in SMK Negeri 1 Beringin - Wati, Lulu Fajar; Efi, Agusti (Universitas Negeri Padang, 2021)
The purpose of this research is to produce valid e-modules based on discovery learning, and effective in basic food subjects. These e-modules based on discovery learning are designed to improve students’ understanding so that it can improve students' learning outcomes. The method in this study uses Research and Development (R&D) with 4-D development procedures (Define, Design, Develop, Disseminate). The data analysis technique uses descriptive analysis techniques to describe the validity, practicality, and effectiveness of e-modules based on discovery learning. The results obtained from this development research: The validity of e-modules based on discovery learning is declared valid on the media and material aspects. The practicality of e-modules based on discovery learning from teacher and student responses is stated to be very practical. The effectiveness of e-modules based on discovery learning is stated to be effective in improving learning outcomes. Based on the findings of this study it is concluded that the e-modules based on discovery learning are valid, practical, and effective to be used as a learning aid in basic food subjects.